MicroRNA-215-3p Suppresses the Growth, Migration, and Invasion of Colorectal Cancer by Targeting FOXM1. (11th October 2019) - Tang, Xiaowei; Shi, Xianfeng; Wang, Nianfei; Peng, Wanren; Cheng, Zhendong
Previous investigations have indicated that microRNA-215-3p is dysregulated in many kinds of cancers and functions as oncogene or tumor suppressor. However, the potential role of microRNA-215-3p in the progression of colorectal cancer remains not well known. Herein, we demonstrated that microRNA-215-3p was downregulated in human colorectal cancer tissues and was reversely correlated to the lymph node metastasis of colorectal cancer. Overexpression of microRNA-215-3p inhibited the clonogenic abilities and metastasis-relevant traits of colorectal cancer cell in vitro . Consistently, upregulation of microRNA-215-3p inhibited the growth and metastasis of colorectal cancer cell in vivo . Forkhead box protein M1 was identified as a direct target of microRNA-215-3p and reexpression of forkhead box protein M1 reversed the suppressive impacts of microRNA-215-3p on the growth, mobility, and invasion abilities of colorectal cancer cell. Altogether, these results revealed the vital role of microRNA-215-3p in the tumorigenesis and metastasis of colorectal cancer.